2009
DOI: 10.1053/j.gastro.2008.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Role of Down-Regulated in Adenoma Anion Exchanger in HCO3– Secretion Across Murine Duodenum

Abstract: Background & Aims-The current model of duodenal HCO 3 -secretion proposes that basal secretion results from Cl -/HCO 3 -exchange whereas cAMP-stimulated secretion depends on a cystic fibrosis transmembrane conductance regulator channel (Cftr)-mediated HCO 3 -conductance. However, discrepancies in applying the model suggest that Cl -/HCO 3 -exchange also contributes to cAMP-stimulated secretion. Of two candidate Cl -/HCO 3 -exchangers, studies of putative anion transporter-1 (Pat-1) knockout (KO) mice find litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 40 publications
7
80
0
Order By: Relevance
“…3, B-D). We conclude that gpSlc26a3 mediates predominantly electroneutral Cl Ϫ /HCO 3 Ϫ exchange, in concert with data reported for human SLC26A3 (8) and mouse Slc26a3 (1,17,26,28,31,58,59). However, functional data on microperfused isolated interlobular ducts suggests that Slc26a3-like, H 2 -DIDS-insensitive Cl Ϫ /HCO 3 Ϫ exchange constitutes only ϳ20% of apical Cl Ϫ /HCO 3 Ϫ exchange under alkaline load conditions (53).…”
Section: C297mentioning
confidence: 42%
“…3, B-D). We conclude that gpSlc26a3 mediates predominantly electroneutral Cl Ϫ /HCO 3 Ϫ exchange, in concert with data reported for human SLC26A3 (8) and mouse Slc26a3 (1,17,26,28,31,58,59). However, functional data on microperfused isolated interlobular ducts suggests that Slc26a3-like, H 2 -DIDS-insensitive Cl Ϫ /HCO 3 Ϫ exchange constitutes only ϳ20% of apical Cl Ϫ /HCO 3 Ϫ exchange under alkaline load conditions (53).…”
Section: C297mentioning
confidence: 42%
“…However, an important function of HCO 3 -secretion in the duodenum is protection of the duodenal epithelium from the acidic chyme delivered from the stomach into the small intestine (Allen and Flemstrom, 2005 of the eutherian duodenum are SLC26A3 and SLC26A6 (Jacob et al, 2002;Singh et al, 2008;Tuo et al, 2006;Walker et al, 2009). However, SLC26A6 contributes little to HCO 3 -secretion (Wang et al, 2005) whereas SLC26A3 is responsible for ~60% of the spontaneous HCO 3 -secretion and ~50% of the cAMP-stimulated secretion, CFTR and a small paracellular leak accounting for the remainder (Walker et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, an important function of HCO 3 -secretion in the duodenum is protection of the duodenal epithelium from the acidic chyme delivered from the stomach into the small intestine (Allen and Flemstrom, 2005 of the eutherian duodenum are SLC26A3 and SLC26A6 (Jacob et al, 2002;Singh et al, 2008;Tuo et al, 2006;Walker et al, 2009). However, SLC26A6 contributes little to HCO 3 -secretion (Wang et al, 2005) whereas SLC26A3 is responsible for ~60% of the spontaneous HCO 3 -secretion and ~50% of the cAMP-stimulated secretion, CFTR and a small paracellular leak accounting for the remainder (Walker et al, 2009). It is generally accepted that SLC26A6 is electrogenic (Jiang et al, 2002;Ko et al, 2002;Xie et al, 2002) with an apparent stoichiometry of 1Cl -:2HCO 3 - (Shcheynikov et al, 2006), and early evidence suggested that SLC26A3 was also electrogenic, but with a stoichiometry of 2Cl -:1HCO 3 -, opposite that of SLC26A6 (Ko et al, 2002;Shcheynikov et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, a similarly patchy DRA immunolabeling pattern was described in duodenal villi (54), and modest DRA labeling was reported in jejunum villi relative to the surface epithelium of the cecum (56), using a different antibody. In our CFTR/DRA double-labeling experiments, DRA was not detected in CHE cells (data not shown).…”
Section: G459 Cftr High Expresser Cellsmentioning
confidence: 99%